San rock art: evidence and argument. (5th June 2015) - Lewis-Williams, J. David; Pearce, David G.
<x content-type="archive" xml:space="preserve">Abstract</x> Whether or not a 'trance-dance' akin to that of today's Kalahari San (Bushmen) was performed by southern /Xam San in the nineteenth century has long been the subject of intense debate. Here the authors point to parallels between nineteenth-century records of San life and beliefs and twentieth-century San ethnography from the Kalahari Desert in order to argue that this cultural practice was shared by these two geographically and chronologically distant groups. More significantly, it is suggested that these ethnographic parallels allow a clearer understanding of the religious and ritual practices depicted in the southern San rock art images.